(untitled) (Global Journal of Human-Social Science, 2019)
Natural hazard are spatial phenomena causing location specific disaster. Disaster previously considered as natural phenomena, is now understood as manifestation of sociocultural environment. Understanding the physical and social vulnerability and risk perception of natural hazard is rising research agenda to help address the issue of social resilience in disaster risk management context. The current study investigate the landslide and flood susceptibility based on multi-criteria analysis and explores risk perception of local people in Gwang Khola watershed of Sindhuli district, Nepal. The study adopted GIS based susceptibility mapping for landslide and flood hazard risk assessment and sample household questionnaire survey, KIS, FGD and field observation to explore risk perception.